Orgavisation of accounting of lease operation in non-profit enterprises - Osadcha, Anna; Chernova, Anna (My University, 2018)
The article is devoted to the substantiation of theoretical, organizational andmethodical principles of accounting of leasing operations in nonprofit enterprises of Ukraine. The view on the accounting of rent transactions to the lessor is presented. The main provisions of the draft international standard "Lease" are considered. Proposed variants of the organization of analytical accounting for individual accounts, which can be used when reflected in the accounting of operating leases.
Keywords: non-profit organization; lease operations; lease